The medieval Merlin tradition in France and Italy prophecy, paradox, and "translatio" - Campbell, Laura Chuhan ca. 20./21. Jh (D.S. Brewer, 2017)
Ideas of translation and adaptation in the middle ages investigated through the lens of the Merlin tradition
Keywords: Merlin -- Fiktive Gestalt -- 540-612; Merlin (Legendary character) in literature; Arthurian romances / History and criticism; French literature / To 1500 / History and criticism; Italian literature / To 1500 / History and criticism; Mündliche Überlieferung; Frankreich; Italien